2009
DOI: 10.1016/j.ijgo.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

A crossover comparison of two types of female condom

Abstract: There were no statistically significantly differences in performance between the 2 types of FCs tested, and most participants would accept using either in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…In the present study, the total failure rate and the frequencies of breakage, misdirection, and slippage were significantly lower for the FC2 than for the PFC. These data differ from those of a study conducted among sex workers in Enping City, China [16], which found the rates of total clinical failure to be similar for both types of FC. This difference might be due to the variation in study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the total failure rate and the frequencies of breakage, misdirection, and slippage were significantly lower for the FC2 than for the PFC. These data differ from those of a study conducted among sex workers in Enping City, China [16], which found the rates of total clinical failure to be similar for both types of FC. This difference might be due to the variation in study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…A more recent study tested improvement in FC knowledge and attitudes among female sex workers after introducing the FC for a period of 2 months; however, the study provided few details on how many of the FCs delivered were actually used or the context of FC adoption 26. A very recent publication compared the clinical features of the original prototype FC produced by the Female Health Company and a similar FC produced in China 27. None of these studies have assessed FC use in the context of MC use among sex workers in China.…”
Section: Introductionmentioning
confidence: 99%
“…The study designs include: Two cluster randomised trials [29,30], ten crossover trials including three noninferiority trials [31][32][33][34][35][36][37][38][39], and three randomized controlled trials [40,41]. See Table 1.…”
Section: Included Studies Study Designsmentioning
confidence: 99%
“…Three studies failed to provide sufficient information and were scored as having unclear risk of bias for both random sequence generation and concealment [31,36]. Three studies reported adequately on the methods of random sequence generation but failed to report on allocation concealment and were scored as having unclear risk of bias for allocation concealment [29,30,37]. The rest of the studies adequately reported random sequence generation and allocation concealment and were judged to have low risk of bias for both domains.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation